PEMANFAATAN PMT KOPEL SEBAGAI SARANA PENGALIHAN BEBAN DI GARDU INDUK SAYUNG KABUPATEN DEMAK - Wibowo, Binka Aji; Manan, Saiful (Gema Teknologi, 2014)
Binka Aji Wibowo, Saiful Manan, in paper use PMT coupling as load transfer in Sayung District Substation, Demak explain that to meet the reliability of the distribution system , it is necessary to do a continuity in the distribution of electrical energy. There are various causes of outages ranging from maintenance to interference. To resolved these problems, there are several solutions that can be done, such as transfer transformer load through PMT coupling. This can be done by connecting the two busbars by using a PMT. In operation the PMT coupling need to do prior preparation, among others, the daily load calculations. It is intended to carry transformer load does not exceed setting value. Keywords : PMT coupling, Busbar, Transformer.